Adipose Tissue-Derived Mesenchymal Stromal Cells Protect Mice Infected with Trypanosoma cruzi from Cardiac Damage through Modulation of Anti-parasite Immunity. - Debora B Mello; Isalira P Ramos; Fernanda C P Mesquita; Guilherme V Brasil; Nazareth N Rocha; Christina M Takiya; Ana Paula C A Lima; Antonio C Campos de Carvalho; Regina S Goldenberg; Adriana B Carvalho (Public Library of Science (PLoS), 2015)
Chagas disease, caused by the protozoan Trypanosoma cruzi (T. cruzi), is a complex disease endemic in Central and South America. It has been gathering interest due to increases in non-vectorial forms of transmission, especially in developed countries. The objective of this work was to investigate if adipose tissue-derived mesenchymal stromal cells (ASC) can alter the course of the disease and attenuate pathology in a mouse model of chagasic cardiomyopathy.ASC were injected intraperitoneally at 3 days post-infection (dpi). Tracking by bioluminescence showed that cells remained in the abdominal cavity for up to 9 days after injection and most of them migrated to the abdominal or subcutaneous fat, an early parasite reservoir. ASC injection resulted in a significant reduction in blood parasitemia, which was followed by a decrease in cardiac tissue inflammation, parasitism and fibrosis at 30 dpi. At the same time point, analyses of cytokine release in cells isolated from the heart and exposed to T. cruzi antigens indicated an anti-inflammatory response in ASC-treated animals. In parallel, splenocytes exposed to the same antigens produced a pro-inflammatory response, which is important for the control of parasite replication, in placebo and ASC-treated groups. However, splenocytes from the ASC group released higher levels of IL-10. At 60 dpi, magnetic resonance imaging revealed that right ventricular (RV) dilation was prevented in ASC-treated mice.In conclusion, the injection of ASC early after T. cruzi infection prevents RV remodeling through the modulation of immune responses. Lymphoid organ response to the parasite promoted the control of parasite burden, while the heart, a target organ of Chagas disease, was protected from damage due to an improved control of inflammation in ASC-treated mice.